Anti-proliferative Activity of Crotalaria pallida Aiton on MCF-7 Breast Cancer Cells - Rumondor, Erladys M.; Moektiwardoyo, Moelyono; Barliana, Melisa I. (Universitas Padjadjaran, Indonesia)
Â Crotalaria pallida Aiton (C. pallida Aiton) is empirically used as dietary supplement to treat cancer by the people of North Sulawesi. However, its scientific pharmacology activity has not been explored yet. Therefore, this study was conducted to evaluate anti-proliferative activity of C. pallida Aiton on MCF-7 breast cancer cells. The extraction of leaves and seeds were performed using ethanol, ethyl acetate, n-hexane, and water. Phytochemical screening was then performed to identify secondary metabolites in this extract. Anti-proliferative activity was evaluated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The results indicated that ethyl acetate fraction of C. pallida Aiton has the lowest IC50 (29,67). In conclusion, ethyl acetate fraction of C. pallida Aiton is potential to be developed as anti cancer agent.Keywords: Crotalaria pallida Aiton, WST assay, MCF-7 cell line